ANALISIS KINERJA JALAN KHATULISTIWA AKIBAT AKTIFITAS PASAR PURING SIANTAN - Fitriyadi, -; S.T., M.T, Sumiyattinah; Kadarini, S.T., M.T, S. Nurlaily. (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
Khatulistiwa Street is a primary highway with national status which connects efficiently between national activity centers or between national activity centers and regional activity centers. As one of the roads which have vital role in traffic in Pontianak City, condition that occurs in the site is very different. At Khatulistiwa Street segment, especially in front of Puring Market frequently occur traffic problems such as increased delays at certain hours. This happens during peak hours or busy hours due to the high activity of the community around the road and the activity of Puring Market at the same time. To improve the performance on Khatulistiwa Street which getting denser, it is necessary to conduct a study in intend to determine the amount of decreasing performance of road segment in the study area. This research is needed to identify problems in Khatulistiwa Street so that later can be found solution to prevent bigger traffic problem happens.In this research, it is necessary to have traffic data i.e. traffic volume, side obstacle, speed, and road geometry so that can be seen and compared how big influence of Puring Market activity to performance on Khatulistiwa Street, so then known how big influence of the increment of the road to the degree of saturation, speed, and travel time. By the results of this study can be seen comparison of data on movement patterns of traffic survey results in 2017, peak hour flow Pontianak - Jungkat direction occurred at 05:00 to 06:00 pm for 1463 vec/hr and for Jungkat - Pontianak direction occurred at 04:00 - 05:00 pm of 1458 vec/hr. Judging from the degree of saturation and travel time that occurred in the site is known that Khatulistiwa Street can be said congested because of the degree of saturation >0.85, that is 0.893 and travel time of light vehicles at 200 meters in distance is 0.0083 hours or 29.77 seconds. The activity of Puring Market towards the performance of Khatulistiwa Street can be said have an effect on the high congestion happened (judging from the comparison of travel time that occurred), that is about 21%. For 9 m wide road and degree of saturation (DJ) of 0.714, the travel time becomes 0.006 hr or 21.662 sec. For 10 m wide road and degree of saturation (DJ) of 0,692, the travel time becomse 0.0057 hr or 20,622 sec. For 11 m wide road and degree of saturation (DJ) equal to 0,666 and travel time become 0.0056 hr or 20,069 sec.Â Keywords: Influence of Market Activity, Traffic Flow, Congestion, Road Khatulistiwa Street is a primary highway with national status which connects efficiently between national activity centers or between national activity centers and regional activity centers. As one of the roads which have vital role in traffic in Pontianak City, condition that occurs in the site is very different. At Khatulistiwa Street segment, especially in front of Puring Market frequently occur traffic problems such as increased delays at certain hours. This happens during peak hours or busy hours due to the high activity of the community around the road and the activity of Puring Market at the same time. To improve the performance on Khatulistiwa Street which getting denser, it is necessary to conduct a study in intend to determine the amount of decreasing performance of road segment in the study area. This research is needed to identify problems in Khatulistiwa Street so that later can be found solution to prevent bigger traffic problem happens.In this research, it is necessary to have traffic data i.e. traffic volume, side obstacle, speed, and road geometry so that can be seen and compared how big influence of Puring Market activity to performance on Khatulistiwa Street, so then known how big influence of the increment of the road to the degree of saturation, speed, and travel time. By the results of this study can be seen comparison of data on movement patterns of traffic survey results in 2017, peak hour flow Pontianak - Jungkat direction occurred at 05:00 to 06:00 pm for 1463 vec/hr and for Jungkat - Pontianak direction occurred at 04:00 - 05:00 pm of 1458 vec/hr. Judging from the degree of saturation and travel time that occurred in the site is known that Khatulistiwa Street can be said congested because of the degree of saturation >0.85, that is 0.893 and travel time of light vehicles at 200 meters in distance is 0.0083 hours or 29.77 seconds. The activity of Puring Market towards the performance of Khatulistiwa Street can be said have an effect on the high congestion happened (judging from the comparison of travel time that occurred), that is about 21%. For 9 m wide road and degree of saturation (DJ) of 0.714, the travel time becomes 0.006 hr or 21.662 sec. For 10 m wide road and degree of saturation (DJ) of 0,692, the travel time becomse 0.0057 hr or 20,622 sec. For 11 m wide road and degree of saturation (DJ) equal to 0,666 and travel time become 0.0056 hr or 20,069 sec.Â Keywords: Influence of Market Activity, Traffic Flow, Congestion, Road